Highly Ordered Hierarchical Pt and PtNi Nanowire Arrays for Enhanced Electrocatalytic Activity toward Methanol Oxidation - Wang, Changzheng; Zhang, Yang; Zhang, Yajun; Xu, Ping; Feng, Cuimin; Chen, Tao; Guo, Tao; Yang, Fengnan; Wang, Qiang; Wang, Jingxiao; Shi, Mengtong; Fan, Louzhen; et al. (ACS applied materials & interfaces, 2018)
Highly ordered hierarchical Pt and PtNi nanowire arrays were prepared using CdS hierarchical nanowire arrays (HNWAs) as sacrificial templates and demonstrated high electrochemical active surface areas. For the resulting Pt HNWAs sample, the peak current for methanol oxidation at +0.74 V was almost 1 order of magnitude higher than that of Pt solid nanowire arrays prepared in a similar manner but without the use of CdS template, and the addition of a Ni cocatalyst effectively enhanced the tolerance against CO poisoning. The results demonstrated that highly ordered Pt and PtNi HNWAs may be exploited as promising anode catalysts in the application of direct methanol fuel cells.